DAMPAK PERLAKUAN PERENDAMAN TERHADAP SIFAT-SIFAT SILVIKULTUR FALOAK (STERCULIA COMOSA WALL) - Fabianus Ranta; Fransiscus X. Dako; Meylin Pathibang (Politeknik Pertanian Negeri Kupang, 2013)
The Effect of Dipping Treatment on Faloak (Sterculiacomosa Wallich) Silviculture Properties. Faloak is a species belongsto dry land that tends to decrease in population and may be endangered because of no silvicultural treatments. This study aims to determine the percentage and growth rate of Faloak at seedling level. A direct test through experimental techniques in nursery plots using complete randomized design (CRD) was used. The results of the study show that the percentage of the growth and the growth rate of Faloak seedlings are different depending on the types of treatments and duration of immersion. It is evident that 3 x 12 hours soaking treatment gives different effects compared to the control (without soaking treatment). The percentation of the growth and growth rate of the faloak increase with the increase of soaking times.Keywords: Sterculiacomosa, Silviculture, Soaking, Percentage of Growth, Growth Rate